Effects of amylin on food intake and body weight via sympathetic innervation of the interscapular brown adipose tissue. (1st February 2022) - Fan, Kuikui; Li, Qiang; Pan, Deng; Liu, Haodong; Li, Penghui; Hai, Rihan; Du, Chenguang
ABSTRACT: Objective: Amylin acts on the lateral dorsal tegmental nucleus (LDT), resulting in anorexic and weight-loss effects and activates thermogenesis in the interscapular brown adipose tissue (IBAT). In addition, it induces neuronal nitric oxide synthase (nNOS) and choline acetyltransferase (ChAT)-mediated feeding. However, the influence of the intact sympathetic nervous system (SNS) in mediating amylin's effects has not been fully characterised. We investigated whether extracellular signal-regulated kinase (ERK), nNOS, and ChAT activities in the LDT are responsible for amylin's anorexigenic effects and whether this requires an intact SNS. Methods: C57BL/6J mice [wild-type (WT), sham, and sympathetic denervation of IBAT] were used. Food consumption, body weight, and distribution of p ERK, nNOS, and ChAT positive neurons in the brain were examined following acute and chronic amylin administration. Results: Food intake was significantly decreased in WT and sham animals following acute amylin injection, but not in the denervated mice. Chronic amylin reduced body weight and serum glucose levels after 6 weeks, but increased insulin levels; no changes were observed in the denervated mice. Acute amylin increased the expression of nNOS, ChAT, and uncoupling protein-1 in the IBAT of WT and sham mice, while no changes were observed in the denervated mice and p ERK from the above effect. Conclusions: Intact SNS of IBAT influences amylin-induced suppression of food intake and body weight, thus affecting nNOS and ChAT signalling in the LDT and locus coeruleus.